ANALISIS PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL PEMEDIASI - Siti Almaidah (STIE Atma Bhakti, 2018)
This study aims to examine and analyze the influence of service quality and company image on customer loyalty mediated customer satisfaction at PT. Bank Jateng Sragen Branch Office. This research is a survey research, in which the research instrument is a questionnaire. The population in this study were customers at PT. Bank Jateng Sragen Branch Office. A sample of 100 respondents was determined by convenience sampling technique. Testing instruments using validity and reliability tests. While the hypothesis test used path analysis with the SPSS program version 20. The results of the study found that: (1) there was a positive and significant influence on service quality and company image on customer satisfaction, (2) there is a positive and significant influence on service quality, corporate image, customer satisfaction on customer loyalty, (3) there is a positive and significant influence on service quality and corporate image on customer loyalty with mediated customer satisfaction.